Resistensi Perempuan Terhadap Ketidakadilan Gender Pada Novel Perempuan Yang Menangis Kepada Bulan Hitam Karya Dian Purnomo - Liya Yuliyani; Maharani Intan Andalas (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This research discusses about the problem of resistance to gender injustice in Dian Purnomo's novel Perempuan yang Menangis kepada Bulan Hitam (PMBH). This study aims to describe and interpret the forms of resistance of women who experience gender injustice and to understand the forms of gender injustice experienced by these female characters. The method used in this study is descriptive qualitative by utilizing feminist literary criticism theory. Data sources are obtained from the entire contents or chapters of the PMBH novel. Data collection techniques using reading and note techniques. The data validity technique of this research is triangulation. The steps in analyzing are: 1) reading the PMBH novel; 2) determine the research focus; 3) marking important parts; 4) sorting data; 5) describe forms of gender inequality and forms of women's resistance; and 6) make conclusions. The results of the analysis show that the forms of gender injustice experienced by the character Magi Diela as the main character and other female characters as subordinate figures are in the form of marginalization, stereotypes, violence, workload, and subordination. The forms of resistance carried out by the character Magi Diela as the main character and other female subordinate figures are in the form of 1) actions and 2) thoughts.